Weavings and Potential of Climate Literacy, Educational Robotics, and Artificial Intelligence in Basic Education - Fornazari, Valeria Brumato Regina; Canazart , Daniele Araujo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This study investigated the effectiveness of an Interdisciplinary Didactic Sequence (IDS) in Middle School, integrating the use of Artificial Intelligence (AI) in the Educational Robotics curriculum, with a focus on Critical Environmental Education to promote Climate Literacy. Methodology – A descriptive analysis was conducted with ninth-grade students and their teacher through the development and implementation of the IDS. Data were collected from student outputs and analyzed descriptively. Originality/Relevance – The study contributes to the discussion on pedagogical innovations in the context of the climate and environmental crisis, the use of educational technologies, and the structuring of new curricular components (BNCC), proposing alternatives for intervention and curricular integration that connect territory and technology through the lens of Critical Environmental Education. Results – The IDS fostered student engagement and protagonism, which can promote the development of critical thinking, authorship, technological and climate literacy, as well as the strengthening of environmental citizenship in the face of the crisis. Theoretical/Methodological Contributions – The study highlights the potential of using AI prompts and tools to mediate learning grounded in Critical Environmental Education for Climate Literacy, as well as the contribution of Educational Robotics to the construction of interdisciplinary projects. Social and Environmental Contributions – The study promoted student protagonism and the ethical use of AI to value local knowledge and foster public debate about real environmental challenges experienced by the community, positioning students at the core of both the crisis and its mitigation.